Cellular changes in bulbar conjunctiva and Vitamin A deficiency. Connection with clinical signs. - Roxana del Carmen Gómez Vilela; Marta Rosa González Deben; Luis Cruz Medina; Dunia Reyes Hernández; Gladys Barberis Pérez (Medisur)
Background: Vitamin A deficiency is followed by keratinization of the mucous membrane that covers the digestive, urinary and respiratory ways. This situation contributes to the emergence of different diseases, mainly infectious illness and elevates mortality and morbidity among children. Objective: To describe the connection between the results of conjunctiva cytology and pathological history of Vitamin A deficiency. Methods: Cross-section study, from September 2003 to March 2004. The sample consisted of 338 children of both genders between 5 and 14 years. The studied variables were: the result of conjunctiva cytology and associated symptoms and individual pathological history. Results: Only 7.4 % of the cytology’s results were normal; the rest was altered, linked to respiratory, digestive and parasitic disorders, among others. Conclusion: Early diagnosis of Vitamin A deficiency can be a prevention method for different common and frequent diseases in pediatric stages.